2011
DOI: 10.1007/s00415-011-6018-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of ALS and LIS patients with and without invasive mechanical ventilation

Abstract: There are very few studies where quality of life (QOL) is assessed in patients with complete physical and functional disability and dependence to invasive mechanical ventilation (IV). We compared QOL of amyotrophic lateral sclerosis (ALS) and locked-in-syndrome (LIS) patients with invasive mechanical ventilation to ALS and LIS patients without mechanical invasive ventilation. Thirty-four patients, 27 with ALS and seven with LIS (vascular or tumoral aetiology) were included in the study. Twelve had invasive ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…The longer patients were in a locked-in state, the higher subjective well-being seemed to be. Another recent study showed that invasive mechanical ventilation for locked-in patients who accept tracheotomy allowed life prolongation without affecting quality of life [72]. Medical teams should be aware of that.…”
Section: Para-clinical Neuroimaging Assessment Independent Of Motor Rmentioning
confidence: 99%
“…The longer patients were in a locked-in state, the higher subjective well-being seemed to be. Another recent study showed that invasive mechanical ventilation for locked-in patients who accept tracheotomy allowed life prolongation without affecting quality of life [72]. Medical teams should be aware of that.…”
Section: Para-clinical Neuroimaging Assessment Independent Of Motor Rmentioning
confidence: 99%
“…Though recent guidelines support the physical benefits of NIV for NMD (Hull et al, 2012), studies suggest that NIV may have both positive (Rousseau, Pietra, Blaya, & Catala, 2011) and negative impacts on psychosocial wellbeing and quality of life (QoL) (Katz et al, 2010;Mah, Thannhauser, McNeil, & Dewey, 2008) Similar to youth with other chronic conditions (Björquist, Nordmark, & Hallström, 2015;Sonneveld et al, 2013) , participants expected to become more autonomous in their health management. In relation to being able plan for the future, participants appreciated the efforts of specialist NMD doctors' to identify their individual diagnosis and the focus this gave.…”
Section: Theme I: Finely Balanced Healthmentioning
confidence: 99%
“…LIS also places a large physical and psychological burden on family members due to the near total absence of the ability to communicate with the individual [1]. In some instances, vertical gaze or eyelid movement is preserved [1], [2], [4], allowing for blink-based or gaze-based communications. However, there are many cases in which individuals do not retain this function [1].…”
Section: Introductionmentioning
confidence: 99%
“…Insult to the ventral pons such as trauma, hemorrhage, or an infarction as well as progression of Amyotrophic Lateral Sclerosis (ALS) can lead to this condition [4]. LIS also places a large physical and psychological burden on family members due to the near total absence of the ability to communicate with the individual [1].…”
Section: Introductionmentioning
confidence: 99%